Multiobjective optimization of laminated composite plates using metaheuristic algorithms - Sager, Guilherme; Hofstadler, Franz; Grotti, Ewerton; Bührer Santana, Pedro; Paucar Casas, Walter Jesus; Gomes, Herbert Martins (Mechanics based design of structures and machines, 2025)
This study introduces a multiobjective optimization algorithm for composite laminates, targeting natural frequencies, internal stresses, and buckling resistance with ply orientation as a primary design variable. Validated against experimental data, the algorithm allows for tailored designs focused on dynamic performance, strength, or buckling needs. Four cases are analyzed, including a graphite-epoxy composite optimized for multiple objectives, showing the significant impact of fiber orientation on achieving specific structural requirements. By generating effective Pareto fronts across varying design constraints, the method provides a scalable approach for complex laminate optimization. This research fills a literature gap, balancing computational efficiency with accuracy compared to benchmark problems.